The IDENTIFIKASI JAMUR PADA ROTI YANG DIJUAL DI KOTA LANGSA BERDASARKAN LAMA PENYIMPANAN - Lestari, Ayu Dinda Lestari (Department of Biology Education, Faculty of Teacher Training and Education, Samudra University, 2019)
Mushroom growth in food is very difficult to prevent. Some types of mushrooms that grow starched are Rhizopus stonolifer, mucor sp, Penicillium sp, Geotrichum sp and Aspergillus sp. The purpose of this study was to determine the growth of mushrooms on Bhoi bread based on storage time and determine what types of mushrooms that grow on Bhoi bread sold in Langsa City based on storage time. The study used Bhoi bread samples which were given 3 treatments namely P1 (left in the open room) P2 (Mushrooms wrapped in plastic mica). The results of this study showed that it began to grow on day 34 and on P3 treatment the fungus began to grow on day 39. The percentage of the amount of mushroom growing on each treatment in P1 was approximately 75%, in P2 treatment it grew approximately 45% and in the treatment, P3 grows approximately 10% of the types of mushrooms that grow on Bhoi bread are Penicillium requantum, Rhizopus stonolifer, Aspergillus fumigatus, Aspergillus niger, Penicillium citrinum and Aspergillis flavus. Bhoi bread storage needs to be done to inhibit the growth of mold using mica plastic.